Disclosure of Student Ability in Working on Higher-Order Thinking Skills Questions through Rasch Modeling - Ade Yulianto; Aan Yuliyanto; Ghullam Hamdu; Lutfi Nur; Desi Fitriani; Noorhisham Hamzah (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractInformation on students' ability in higher-order thinking obtained during the learning process can certainly provide an overview for teachers to evaluate appropriate and effective learning. In this context, how can a teacher properly carry out diagnostic and remedial teaching based on the information on student abilities obtained? Therefore, this study aims to provide a disclosure analysis technique for the acquisition of students' abilities in higher-order thinking. This research is one of the stages of Design-Based Research (DBR), which is a reflection to produce design principles and perfect their implementation. Determination of the research sample is done by using the purposive sampling technique. Data collection of students' ability in higher-order thinking was done through HOTS-based test questions developed based on the cognitive hierarchy adopted from Bloom's taxonomy. The results of the acquisition of students' abilities in higher-order thinking were then analyzed through Rasch modeling with the help of the Winsteps 3.75 application. Based on the results of Rasch modeling, it was obtained that the students' abilities were grouped into high, medium, and low categories and had a level of suitability of abilities that did not need to be reviewed, and there were no biased student abilities. The results of data processing and analysis of students' ability in higher-order thinking have implications for teacher actions in carrying out appropriate and effective learning evaluations as well as mapping students' abilities in higher-order thinking with unbiased conformity.Keywords: student ability, HOTS-based test questions, rasch modeling. AbstrakInformasi kemampuan siswa dalam berpikir tingkat tinggi yang diperoleh selama proses pembelajaran tentunya dapat memberikan gambaran bagi guru untuk melakukan evaluasi pembelajaran yang tepat dan efektif. Dalam konteks tersebut, bagaimana seorang guru dapat secara tepat melakukan diagnostic and remedial teaching berdasarkan informasi kemampuan siswa yang diperoleh?. Maka dari itu, penelitian ini bertujuan untuk memberikan teknik analisis pengungkapan pemerolehan kemampuan siswa dalam berpikir tingkat tinggi. Penelitian ini merupakan salah satu tahapan dari Desain Based Reaserch (DBR), yakni refleksi untuk menghasilkan prinsip-prinsip desain dan menyempurnakan implementasinya. Penentuan sampel penelitian dilakukan dengan menggunakan teknik purposive sampling. Pengumpulan data kemampuan siswa dalam berpikir tingkat tinggi dilakukan melalui pengerjaan soal tes berbasis HOTS yang dikembangkan berdasarkan hirarki kognitif yang diadopsi dari taksonomi Bloom. Hasil pemerolehan kemampuan siswa dalam berpikir tingkat tinggi kemudian dianalisis melalui pemodelan rasch dengan berbantuan aplikasi winsteps 3.75. Berdasarkan hasil pemodelan Rasch diperolehlah pengelompokkan kemampuan siswa dengan kategori tinggi, sedang, dan rendah serta memiliki tingkat kesesuaian kemampuan yang tidak perlu ditinjau ulang dan tidak terdapat kemampuan siswa yang bias. Hasil pengolahan dan analisis data kemampuan siswa dalam berpikir tingkat tinggi berimplikasi pada tindakan guru dalam melaksanakan evaluasi pembelajaran yang tepat dan efektif serta pemetaan kemampuan siswa dalam berpikir tingkat tinggi dengan kesesuaian yang tidak bias.Kata kunci: kemampuan siswa, soal tes berbasais HOTS, pemodelan rasch.